Pemetaan batimetri dan pemodelan morfologi dasar danau serta analisa daya tampung genangan Danau Patenggang - Adithya Kresna Sumaamijaya; Fazel Karly; Nandra Ramira Ar; Haikal Muhammad Ihsan (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
This research aims to map the bathymetry and model the bottom morphology of Patenggang Lake and analyze the lake's inundation capacity. This mapping is important because detailed spatial and morphometric data is not yet available as a basis for planning the management and sustainable use of water resources in the area. The research was conducted through mechanical depth measurement, using a measuring stick for shallow areas and a weighted measuring tape for the middle of the lake. The depth data collected was then processed using the topo to raster interpolation method in ArcGIS software to produce a hydrologically accurate digital elevation model (DEM). The DEM became the basis for analyzing the shape and topographic structure of the lake bed. The results show that Patenggang Lake has a basic morphology in the form of a bowl-like basin, with a maximum depth of 12.5 meters in the northwest and a minimum depth of 3 meters in the northeast. The topographic characteristics of the bottom vary: the northwest is relatively gentle, the northeast is moderately gentle, the southeast is moderately steep, and the northwest is very steep. The storage capacity analysis showed that the surface area and water volume increased linearly with elevation, but at different rates of increase. These main results show that elevation changes greatly affect the lake's storage capacity and have implications for the stability of its hydrological functions. This research provides scientific contributions in the form of basic morphometric data and the latest bathymetry model that can be used in lake ecosystem management. Practically, these results can serve as the basis for technical planning of Lake Patenggang water resources management, especially to support conservation, water quality control, irrigation, and development of tourism potential based on accurate spatial data.